Quartz Tube Enhanced Raman Scattering Spectroscopy - Si, Ganshang; Liu, Jiaxiang; Li, Zhengang; Ning, Zhiqiang; Fang, Yonghua (Frontiers in Physics, 2022)
Raman spectroscopy is widely used in many fields with the advantages of simultaneous species detection and molecular fingerprint characteristics, but the low detection sensitivity limits its further development, especially for highly scattering or turbid mediums. In this consideration, a new method called quartz tube enhanced Raman scattering spectroscopy was proposed for the first time in this paper. A quartz tube was inserted into the powder sample to improve the coupling of light into the medium and increase the interaction volume of the laser with the sample (“volume-excitation”), multiple scattering of the light within the turbid medium resulted in an increased Raman signal. In this paper, the effect of different sizes of quartz tubes on the sensitivity enhancement was studied. The results show that the enhancement factor of the signal intensity was nearly 5.37 (the Raman signal of HCO3-) compared to traditional Raman spectroscopy technology. Furthermore, the method was successfully applied to improve the Raman signal intensity of the mixed sample (1:5, m(PO43-):m(HCO3-)) and detect the baking soda powder buried under a 6 mm thick layer of potassium dihydrogen phosphate powder. The results show that the technology will open a new way for the quantitative analysis and detection of powder samples.